Properties of the modulus of continuity for monotonous convex functions and applications - Sorin Gheorghe Gal (International Journal of Mathematics and Mathematical Sciences, 1995)
For a monotone convex function f∈C[a,b] we prove that the modulus of continuity w(f;h) is concave on [a,b] as function of h. Applications to approximation theory are obtained.